The Impact of Privacy Laws on Social Media in the United Arab Emirates - ALHAMMADI, ABDELRAHMAN AHMED ALMULLA (2018)
The purpose of this research is to perform a study on the impact of privacy laws on social media. This discussion demonstrates that there is no single definition of privacy that is applicable to all features of social media and that it is often necessary to combine perspectives to achieve a holistic framework that can guide research on issues of both information disclosure and privacy. This research is based on an Epistemology research methodology; as this methodology is focused on the facts that determine the acceptable knowledge about the concerned field of research as well as it also question the information known to be true on the basis of rigorously tested and treated facts. Furthermore, results examined that social networking privacy laws are followed by the UAE social networking websites but not by all. In the conclusion of this research, the measures to determine the privacy law’s impact on personal information policies, control and notification to measure the acceptance of social networking websites by users and risk awareness in determining social networking acceptance by users are discussed. And the results concluded that that privacy laws and concerns for control and notification affected the user's acceptable behavior and the UAE authorities must follow such measures that guarantee the protection of sensitive information and other personal details